Implementing SAK ETAP on the Quality of SMEs Financial Reporting: Case Study of Batik SMEs - Luluk Muhimatul Ifada; Sri Anik; Fatmasari Sukesti; Andwiani Sinar Asri (Universitas Pendidikan Indonesia, 2022)
This study examines the relationship between SAK ETAP (Financial Accounting Standards for Entities Without Public Accountability) socialization, understanding of accounting, and motivation to prepare financial statements as independent variables on the quality of SMEs financial reporting in Pati, Central Java, Indonesia. This study used a purposive sampling method for 30 Batik SMEs. This study used primary data processed by the multiple linear regression analysis with SPSS and shows a significant positive relationship. Financial reports on SME operations aim to provide information on the financial position, financial performance, and cash flows needed by stakeholders to continue their business. This study determines the role of SMEs by presenting financial reports that have been determined in accordance with SAK ETAP. The test results in this study indicate that the socialization of SAK ETAP, understanding of accounting, and motivation to prepare financial statements positively affect the quality of financial reporting for SMEs.